FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN NELAYAN DI DESA BAHONSUAI KECAMATAN BUMI RAYA KABUPATEN MOROWALI - Husnul Fial; Siti Yuliaty Chansa (Universitas Tadulako, 2022)
This study aims to determine the effect of working capital factors, length of time at sea, ship engine, miliage at sea, and fishing experience onfishermen in bahoncustom village, morowali regency. The analytical tool used is the coeficient of determination test. And the simultaneous test.the results of this study are the variables of working capital, length of time at sea, ship engine, miliage at sea, and experience at sea have a positive influence on fishermen’sincome when working capital factors, length of time at sea, the boat engine, fishing distance, and fishing experience increase, so the income of fishermen will also increase.The conclusion in this study is that there is a significant influence between the variabels of working capital,lenght of time at sea,and fishing experience on fishermens income. It is recommended that fishermen access information that is aseful for their income.